The impact of heavy metals on plant organisms and methods of their analysis: an overview - Kaverina , M.; Ualiyeva , R.; Syso , A. (Fundamental and Experimental Biology, 2025)
This review provides a detailed analysis of the impact of heavy metals on plant organisms, with a focus on the specific issue of aluminum toxicity in Kazakhstan’s industrial regions. The rapid expansion of mining and metallurgical industries has resulted in elevated pollutant emissions, with aluminum posing a significant environmental risk. Unlike other metals, its phytotoxicity manifests indirectly through soil acidification caused by acid rain (resulting from SO₂ and NOₓ emissions), which mobilizes toxic Al³⁺ ions from aluminosilicates. The Pavlodar region serves as a case study to examine secondary aluminum contamination and its major effects on plant roots, including growth inhibition, cytoskeleton disruption, mineral nutrient imbalance, and oxidative stress. The review compiles data on heavy metal accumulation in plants across Kazakhstan and critically evaluates advanced analytical techniques (ICP-MS, XAS, EXAFS) that are essential for determining aluminum bioavailability and toxicity. It also highlights the role of plants as bioindicators and the potential of phytoremediation technologies. Based on current research, the review recommends adaptive measures for Kazakhstan, including soil liming, the use of aluminum-tolerant plant species, and implementation of modern environmental monitoring to reduce ecological risks and maintain ecosystem productivity